Math Creativity Survey For Class 4 Elementary School - Arnelia Dwi Yasa; Denna Delawanti Chrisyarani; Ludovikus Boman Wadu; Aji Prasetya Wibawa; Dedy Kuswandi (Jurnal Ilmiah Sekolah Dasar, 2021)
Problems in mathematics are increasingly complicated, especially related to students' creativity. The fundamental problem of learning mathematics is that learning is difficult and tedious and impacts students' learning outcomes. It needs special attention so that students' creative abilities in mathematics must be developed in various ways. The purpose of this study is to analyze the creativity of elementary school students in learning Mathematics. This research uses a descriptive approach in the form of a survey. This study involved 200 students from 11 elementary schools. The research instrument is a questionnaire based on four aspects: flexibility, originality, and elaboration. A descriptive approach was used to analyze the research data. The findings show that students' creativity differs in four aspects. The Fluency Aspect got a score of 3.07 in the medium category. The flexibility aspect got a score of 3,098 in the medium category. The originality aspect got a score of 2.37 in the medium category. The aspect elaboration got a score of 2.47 in the medium category. Based on the study results, it can be found that from the four aspects of student creativity in the medium category. The findings state that sub-indicators in every aspect of creativity need to be developed and improved.